2016
DOI: 10.1186/s12889-016-3609-5
|View full text |Cite
|
Sign up to set email alerts
|

Can socio-economic differences explain low expectation of health services among HIV patients compared to non-HIV counterparts?

Abstract: BackgroundThe health service of China has encountered significant challenges due to inequalities in socio-economic determinants of health. HIV patients are known to suffer from social stigma, and may receive inadequate responsiveness from health providers. Before assessing the responsiveness they receive, it is important to know their expectations. We aimed to compare levels of expectation towards the healthcare service among HIV and non-HIV patients with adjustment for socio-economic factors.MethodsA cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…One study comparing healthcare expectations between patients with and without HIV (human immunodeficiency virus infection) showed that disease-related stigma could influence the level of patient expectation and that statistical differences were found in all eight domains of responsiveness. 27 In China, mental disorders are also associated with stigma, and patients with mental disorders are likely to have negative experiences and discrimination when receiving health services. 49,50 However, statistical differences of expectations between patients from the MHD and ED were only detected in two domains in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study comparing healthcare expectations between patients with and without HIV (human immunodeficiency virus infection) showed that disease-related stigma could influence the level of patient expectation and that statistical differences were found in all eight domains of responsiveness. 27 In China, mental disorders are also associated with stigma, and patients with mental disorders are likely to have negative experiences and discrimination when receiving health services. 49,50 However, statistical differences of expectations between patients from the MHD and ED were only detected in two domains in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, stigma of HIV is still serious in China 52 and is identified as an explanation for HIV patients' much lower expectations for health services. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two hospitals have the largest number of admissions of HIV and non-HIV-infectious patients in Yunnan. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that the expectations of HIV patients among the eight domains were lower than that of non-HIV patients, and the assessment of HSR based on HIV patient’s perceptions may give biased results toward the quality of HIV services. 14 Thus, studies are needed to compare differences in HSR based on patients’ experience of health care service simultaneously.…”
Section: Introductionmentioning
confidence: 99%